EVP Strategy for Islamic Boarding Schools: Balancing Formal Recognition and Charismatic Legitimacy for Retention - Siti Aimah; Nihayatul Wafiroh; Nur Wiarsih; Fathiyah Mohd Fakruddin (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
Harmonization between formal recognition and charismatic legitimacy is crucial to addressing the challenges of educator retention, in order to ensure the sustainability of professional human resource management without neglecting the traditional values ??and spirituality typical of the Islamic boarding school environment. This study aims to analyze a unique and effective Employee Value Proposition (EVP) strategy in Islamic boarding schools to improve the retention of qualified educators, especially amidst the increasing demands for professionalism that prioritize formal qualifications. Using a qualitative approach with a case study type. Data were collected through participant observation, in-depth interviews with Kyai, administrators, and educators from various.. Data analysis using interactive models and data examination using triangulation. The results show that the EVP at Darussalam Blokagung Islamic Boarding School is effective through a dual-factor harmonization model. This strategy balances Formal Recognition with Charismatic Legitimacy as the Essential Motivating Factors for retention. Harmonization is supported by EVP Segmentation and the role of Harmonious Alumni, which binds core talent to spiritual commitment. This redefines retention in value-based institutions by combining external professionalism and internal charismatic authority. This research contribution offers a conceptual model of the Dual-Factor EVP of Islamic Boarding Schools that harmoniously integrates the values ??of spirituality (charisma) and local culture (khidmah) into a contemporary Human Resource Management framework, providing practical and strategic guidance for community-based educational institutions to manage and retain superior talent amidst value disruption and intense competition.